STRATEGI PENGUATAN KAPASITAS STAKEHOLDER DALAM ADAPTASI DAN MITIGASI BANJIR DI KOTA SURAKARTA - Muzakar Isa; M. Farid Wajdi; Syamsudin Syamsudin; Anton Agus Setyawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2013)
The objectives of the study are: to analyze the level of preparedness of the stakeholdersin the adaptation and mitigation of floods in Surakarta, and to develop strategies to strengthen thecapacity of adaptation and mitigation of floods in Surakarta. Mixed-method of quantitative andqualitative has been employed to develop the strategy posed. The competent 15 keypersons wereselected using purposive quoted sampling for interview. Descriptive statistics and AHP wereemployed to analize the data. The results showed that that the stakeholders do not yet optimal inmitigation and adaptation to flooding. Capacity building strategy can be done through (a)developa strategic plan for overcoming Flood, (b) education, training and socialization of the adaptation and mitigation of flooding, (c) development and improvement of the physical aspects, (d)publicparticipation in flood mitigation, (e) planning and provision of logistics, funding, and equipment,(f) preparation of SOP flooding, and (g) encourage the protection of assets through insurance.